THE EFFECT OF RETAILING MIX ON CONSUMER DECISIONS TO SHOPPING AT MAIMART SHOP, BIMA CITY - yuyun yulianti; Herry Nurdin (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effect of the Retailing Mix on consumer decisions to shop at the convenience store of Maimart Kota Bima. The variables in this study include location, product, price, promotion, service, and consumer decisions. The population in this study are all consumers who shop at the convenience store of Maimart Kota Bima whose number is not known with certainty. Sampling technique using accidental sampling method, namely the determination of the sample based on need, that is, anyone who happens to meet the researcher can be used as s sample. Then obtained a total sample of 50 respondents. Data collection method with questionnaires, dat analysis using multiple linear regression analysis. The results of the study using factor analysis show that there are 25 indilators that form 6 factors, namely location, product, price, promotion, service and consumer decisions factors, the results of multiple linear regression show the factors of location, product, price, promotion, service and consumer decisions together-ama has a significant effect on consumer decisions.